2008
DOI: 10.1002/pon.1342
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a longitudinal study of changes in cognitive function in breast cancer patients undergoing chemotherapy with doxorubicin and cyclophosphamide

Abstract: Data from this study supported the hypothesis that chemotherapy may have a negative impact on select domains of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 27 publications
(64 reference statements)
4
95
2
8
Order By: Relevance
“…One cross-sectional study of 134 BCS found that higher levels of attentional fatigue were related to more depression and physical fatigue and to lower levels of physical functioning and psychological well-being. 8 Additional evidence suggests that BCS with greater attentional fatigue also experience greater mood disturbance, 8 depression, 12,13 and overall poorer quality of life. 12 However, little is known regarding the impact of attentional fatigue on work ability.…”
Section: -4mentioning
confidence: 99%
“…One cross-sectional study of 134 BCS found that higher levels of attentional fatigue were related to more depression and physical fatigue and to lower levels of physical functioning and psychological well-being. 8 Additional evidence suggests that BCS with greater attentional fatigue also experience greater mood disturbance, 8 depression, 12,13 and overall poorer quality of life. 12 However, little is known regarding the impact of attentional fatigue on work ability.…”
Section: -4mentioning
confidence: 99%
“…-La quimioterapia adyuvante puede producir deterioro cognitivo persistente en el tiempo en un subgrupo de pacientes (8,11) , mientras que en otros casos puede haber una tendencia a la recuperación con el paso del tiempo (12)(13)(14) .…”
Section: Estudios Longitudinalesunclassified
“…-Algunos dominios cognitivos pueden tener mayor propensión a sufrir deterioro (ver Tabla 1) (8,(13)(14)(15) -El déficit puede mantener una relación dosis-dependiente, presentando mayor riesgo las mujeres que reciben quimioterapia a dosis altas (16) . -La combinación de tratamientos antineoplásicos, por ejemplo quimioterapia más tamoxifeno, puede provocar alteraciones cognitivas más severas (10) .…”
Section: Estudios Longitudinalesunclassified
See 1 more Smart Citation
“…A number of mechanisms through which CRCI may arise have been proposed. For example, Jansen et al (2008) and Myers (2009) hypothesised that CRCI occurs in response to the release of cytokines as a result of treatment. Dietrich, Han, Yang, MayerProschel and Noble (2006) argued that CRCI occurs because chemotherapy is more harmful to brain cells than cancer cells and thus causes brain damage leading to cognitive impairment before the cancer cells have been eradicated.…”
Section: Introductionmentioning
confidence: 99%